The Mesoscale Gravity Wave Response to the 2022 Tonga Volcanic Eruption: AIRS and MLS Satellite Observations and Source Backtracing. Issue 10 (21st May 2022) - Ern, M.; Hoffmann, L.; Rhode, S.; Preusse, P.
Abstract: On 15 January 2022, the Hunga Tonga–Hunga Ha'apai volcano erupted violently. This exceptional event excited a manifold of atmospheric waves. Here, we focus on the mesoscale part of the wave spectrum. About 8.5 hr after the eruption a strong atmospheric gravity wave (GW) was observed in the stratosphere by the satellite instruments Atmospheric Infrared Sounder (AIRS) and Microwave Limb Sounder (MLS) in the vicinity of Tonga. By ray‐tracing, we confirm the eruption as the source of this GW event. We determine the wave characteristics of the GW in terms of horizontal and vertical wavelengths and GW momentum flux. The strength of the GW is compared to the usual Southern Hemisphere flux values during this week. The event is comparable to the strongest convective events considering MLS, and exceptionally strong considering AIRS, which observes faster waves only. Plain Language Summary: Atmospheric gravity waves (GWs) are small‐ and mesoscale waves typically generated by convective events, jet instabilities, or flow over orography. On 15 January 2022, an explosive eruption of the Hunga Tonga–Hunga Ha'apai volcano occurred. This eruption was a source of strong GWs of a wide range of wavelengths and phase speeds. We here focus on mesoscale waves and in particular on vertical wavelengths with the potential for interaction with the background wind, that is, vertical scales usually considered for driving atmospheric circulation. Observations by two different types of satellite instruments (limb sounding and nadir sounding) give us the unique opportunity for a detailed study of this GW event originating from a source process that has rarely been considered so far. Tracing the wave backward in time using a wave‐propagation model confirms the volcanic eruption as the wave source. Horizontal and vertical wavelengths of the GW are 500 and 20 km, respectively. Amplitudes and momentum flux indicate that the event is outstanding in particular for the higher phase speeds. We consider this rare wave event highly interesting for future more detailed observational studies, as well as for atmospheric modeling. Key Points: On 15 January 2022, a wide variety of gravity wave scales were excited by the eruption of the Hunga Tonga‐Hunga Ha'apai volcano We here focus on characterizing and quantifying the mesoscale response and confirm by backtracing the eruption as source of these waves Compared to usual conditions amplitudes and momentum flux of the eruption wave event are strong for Microwave Limb Sounder and exceptional for Atmospheric Infrared Sounder